ICT infrastructure and social media tools usage in disaster/crisis management - Ankur Chaturvedi; Anoop Simha; Zhen Wang (International Telecommunications Society (ITS), 2015)
This article explores the ICT infrastructure enabling social media usage for disaster management. In the era of pervasive social media, the study seeks to probe the usage of social media tools and functionalities in times of disasters. The study deploys Grounded Theory approach. Extending on disaster management cycle, this study examines the various source of information in social media followed by the type of information disseminated by them and additionally the most extensively used form of information. Three recent catastrophic events in disaster-prone Asia Pacific region were selected, Kashmir floods (September 2014), Indonesia landslide (December 2014), and Cyclone Pam (March 2015). Twitter was deployed for data collection under two phases, immediately aftermath of the event and a random sample from the first 5 days of the event. These two data sets examined the research questions by presenting timely and panoramic dimensions. The study is novel since it extends the literature on disaster management by providing a content analysis of social media instead of relying on self-reported data by comparing and contrasting across disasters. The triangulations between the qualitative and quantitative methods were adopted to check the results. Drawing the principles of grounded theory, a framework is proposed accordingly with key focus on information flow. In the existing ICT Infrastructure, social media tools have the capability of effectively diffusing the information from perspective of the sources and the available functionalities. Data suggested new insights in context of socio-cultural aspect, and development, which imply on the level of ICT infrastructure. In the end the study proposes certain practical and policy implications highlighting the changing trends of information consumption traits.
Keywords: 330; ICT; social media; information flow; disaster; crisis; kashmir floods; indonesia landslides; cyclone pam